Konsep Epe Ndaet Millah: Unsur-Unsur Ruang Permukiman Kampung Makaling, Papua Selatan - Hematang, Yashinta Irma Pratami; Sastrosasmito, Sudaryono; Kurniawan, Harry (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
The Malind Anim Tribe is unique and has been famous since the colonial era in Papua. The Malind Duh tribe, as one of the Malind Anim sub-tribes, still lives in Makaling Village on the coast of Merauke, South Papua. Their residential space has a local concept of forming elements, which is then known as the concept of epe ndaet millah. To support development in South Papua and its surroundings, the Indonesian government has prepared regulations and policies as well as development activities to improve the welfare of the Papuan people. This research used a qualitative inductive phenomenological method, which has the potential to minimize the gap between prescriptive premises in development planning and the empirical reality at the research location. The aim is to describe the concept of epe ndaet millah that lives in Makaling Village, Okaba District, Merauke Regency, South Papua Province. This research described the elements that form the Kampung Makaling, namely in two constituent aspects, namely the ahhidih and the mbya no idihe, both of which are elements that complement each other as a unit. The layers of elements of the Makaling’s settlement in the epe ndaet millah concept make it a unique concept and has local wisdom, useful for research studies on residential and urban spaces in other areas and for practical use in the concept of designing settlements and urban spaces in South Papua and its surroundings.